Adaptation of Archaeal Communities to Summer Hypoxia in the Sediment of Bohai Sea - Xiaoxiao Guo; Yanying Li; Guisheng Song; Liang Zhao; Jing Wang (Ecology and Evolution)
ABSTRACT Understanding the adaptation of archaea to hypoxia is essential for deciphering the functions and mechanisms of microbes when suffering environmental changes. However, the dynamics and responses of archaea to the sedimentary hypoxia in Bohai Sea are still unclear. In this study, the diversity, composition, and distribution of archaeal community in sediment along an inshore–offshore transect across the oxygen‐depleted area in the Bohai Sea were investigated in June, July, and August of 2021 by employing high‐throughput sequencing of 16S rRNA gene. Results indicated that the archaeal communities were dominated by Thermoproteota (80.61%), Asgardarchaeota (8.70%), and Thermoplasmatota (5.27%). Dissolved oxygen (DO) and NO3− were the two key factors shaping the distribution of archaeal communities, accounting for 49.5% and 38.3% of the total variabilities (p < 0.05), respectively. With the intensity of oxygen depletion, the diversity of archaeal communities increased significantly. Microbial networks revealed that Bathyarchaeia played a key role in interacting with both bacteria and other archaeal groups. Furthermore, adaptions to hypoxia of archaea were also displayed by variation in relative abundance of the predicted ecological functions and the metabolic pathways. The enrichment of specific nitrogen transformation enzymes showed the potential for nitrogen fixation and removal, which might contribute to the balance of N budget and thus facilitate the ecological restoration under eutrophication in Bohai Sea. Our results provided a new picture on ecological and metabolic adaptions to hypoxia by archaea, which will be beneficial to further investigations in extreme environments both theoretically and practically.